Reducing Recovery Times in Outpatient Liver Biopsies: Role of the GI Nurse. (13th July 2022) - Kelly, Lisa; Simon, Peter; Nash, Angela; Thompson, Julie; Affronti, Mary Lou
Abstract : This project is aimed to identify whether recovery times could be reduced in patients undergoing an outpatient liver biopsy. Liver biopsies are typically performed in a hospital setting, and many facilities require patients to recover for multiple hours, sometimes ranging from 4 to 6 hours. This can discourage the patient from undergoing the biopsy. Multiple studies have examined recovery times and determined patients can safely recover and be discharged within 1–2 hours post-liver biopsy. In this retrospective review, the data of 60 outpatients who underwent a liver biopsy from June to December 2020 were analyzed. Analysis included comparing vital signs and symptoms at the 2-hour recovery period and 4-hour discharge time also to see whether there were any hospital admissions 1 week post-liver biopsy. Descriptive statistics were utilized for the data collected in this study. Results demonstrated that after 2 hours, 55 (91.7%) patients had vital signs within safe parameters, pain less than 5 on a 10-point pain scale and denied any other symptoms. The remaining five patients (8.3%) did not meet discharge criteria at the 2-hour mark because of pain greater than 5 on the pain scale yet were still discharged safely at the 4-hour mark.